Le motif du vagabondage dans quelques nouvelles « noires » d’Émile Zola - Kaczmarek, Anna (Quêtes littéraires, 2014)
The paper shows the importance of the motif of vagabondage recurrent in three of Zola’s short stories: For a Night of Love, Jacques Damour and The Death of Olivier Becaille. Their characters’ aimless wandering through the coutryside, through France or the entire world either means perfect happiness, time-filling strategy, or consequence of one’s past or bad luck. It is aways opposed to immobility of sleep or death.